Implementation of Job Position and Workload Analysis in Filling Formation for State Civil Apparatus Requirements in Lahat Regency in 2021 - Muhammad Deswan Dinata; Indu Yeliana (Gayaku Publisher, 2023)
This study aims to find out the results of applying job and workload analysis in filling the form of the needs of the state civil apparatus in Lahat Regency in 2021. The research design uses a qualitative descriptive. The research instrument was the researcher himself, using guide materials and interview results. Data collection techniques from interviews, relevant documents, and publication documents. Testing the correctness of the data by way of source triangulation. Data analysis consisted of four stages, namely, collecting, reducing, and presenting data and drawing conclusions. The results of this study are that the implementation of the analysis of positions and workload in filling out the formation needs of the state civil apparatus in Lahat Regency is already good with a formation occupancy of 93.5% for CPNS formations and good enough for PPPK formations with a formation occupancy of 65.9%. The organizational division as the spearhead of implementing job and workload analysis can provide the widest possible space and time for personnel managers in each regional apparatus to consult so that they can understand and carry out job and workload analysis on their regional apparatus following the rules and what is the goal the organization can be achieved, in addition to that part of the organization should be able to plan activities that are precise, clear and accurate so that the use of the budget for these activities can be addressed and adequate.